A Novel Tetramethylpyrazine Derivative Protects Against Glutamate-Induced Cytotoxicity Through PGC1α/Nrf2 and PI3K/Akt Signaling Pathways - Chen, Haiyun; Cao, Jie; Zhu, Zeyu; Zhang, Gaoxiao; Shan, Luchen; Yu, Pei; Wang, Yuqiang; Sun, Yewei; Zhang, Zaijun (Frontiers in Neuroscience, 2018)
Glutamate-induced excitotoxicity is one of the main causes of neuronal cell death in stroke. Compound 22a has been previously reported as a promising neuroprotective compound derived from tetramethylpyrazine, which is a widely used active ingredient of traditional Chinese medicine Chuanxiong (Ligusticum wallichii Franchat). Compound 22a can protect neurons from oxidative stress-induced PC12 cell death and alleviates the infarct areas and brain edema in a rat permanent middle cerebral artery occlusion model. In the current work, we further investigated the neuroprotective effects and underlying mechanisms of compound 22a against glutamate-induced excitotoxicity in primary culture of rat cerebellar granule neurons (CGNs). We found that pretreatment with compound 22a prevented glutamate-induced neuronal damage by maintaining mitochondrial membrane potential and attenuating cellular apoptosis. Compound 22a could also enhance peroxisome proliferator-activated receptor gamma coactivator 1-alpha (PGC1α) transcriptional activity and induce nuclear accumulation of Nrf2 in PC12 cells. Accordingly, pretreatment with compound 22a reversed the glutamate-induced down-regulation of expression of the proteins PGC1α, transcriptional factor NF-E2-related factor 2 (Nrf2), and hemooxygenase 1 (HO-1). In addition, compound 22a increased the phosphorylation of phosphoinositide 3-kinase (p-PI3K), phosphorylated protein kinase B (p-Akt), and glycogen synthase kinase 3β (p-GSK3β). Meanwhile, the small interfering RNA-mediated silencing of PGC1α expression and selective inhibitors targeting PI3K/Akt (LY294002 and Akt-iv) could significantly attenuate the neuroprotective effect of compound 22a. Taken together, compound 22a protected against glutamate-induced CGN injury possibly in part through regulation of PGC1α/Nrf2 and PI3K/Akt pathways.